Vascularization of artificial beds for pancreatic islet transplantation in a rat model - Kriz, J; Jirak, D; Vilk, G J; Girman, P; White, D J; Hajek, M; Saudek, F (Transplantation proceedings, 2010)
An alternative prevascularized bed with a subcutaneously located entrance would substantially improve islet engraftment, requiring much less invasive surgery. Studies have described times necessary for the creation of an artificial pouch suitable for subsequent islet transplantation. Polymeric mesh shaped in rounded scaffolds were implanted both subcutaneously and into the major omentum of Brown Norway female rats (n = 7). The connective tissue together with vessels were embedded into scaffolds at 1 week without regard to site. In contrast to the major omentum, vessels within the subcutaneous connective tissue surrounding the devices started to decline in 2 weeks and almost disappeared 1 week later. Magnetic resonance imaging (MRI) detected changes in fibrous tissue surrounding the wall, but only large veins located beside the devices were visible using basic MRI. The blood supply to the internal surface of the created beds was important for islet engraftment, but information could be obtained only by using dynamic contrast-enhanced MRI.
Keywords: Animals; kosterní svaly; Islets of Langerhans Transplantation; Magnetic Resonance Imaging; Pain, Postoperative; Langerhansovy ostrůvky; Female; Analgesics, Opioid; potkani inbrední BN; transplantace Langerhansových ostrůvků; Prostheses and Implants; ženské pohlaví; erytrocyty; Islets of Langerhans; Omentum; Rats, Inbred BN; tramadol; magnetická rezonanční tomografie; Muscle, Skeletal; Models, Animal; opioidní analgetika; omentum; Erythrocytes; Tramadol; krysa rodu Rattus; pooperační bolest; protézy a implantáty; zvířata; Rats; modely u zvířat